Inequality in minimum-effort coordination - Christoph Feldhaus; Bettina Rockenbach; Christopher Zeppenfeld (ZBW - Leibniz Information Centre for Economics, 2020)
Successful coordination is key for economic and societal wealth. The rich literature on the minimum-effort game (MEG) has provided valuable insights into coordination, both theoretically and empirically. Yet, although real-world scenarios often involve asymmetric benefits and/or costs from coordination, most previous studies rely on symmetric MEGs. We investigate the effect of unequal equilibrium pay-offs in the MEG. In two experiments, we observe that players are better able to coordinate on an equal rather than an unequal Pareto-dominant equilibrium. We find that the ability to coordinate on the unequal Pareto-dominant equilibrium critically hinges on the costs of miscoordination for the player who benefits most from successful coordination: when her costs are low, she seems able to stabilize the Pareto-dominant equilibrium even if payoffs are highly unequal, whereas coordination success worsens substantially when her costs are high.
Keywords: C72; C92; 330; minimum effort game; coordination; social comparison; potential games; lab experiment